2005
DOI: 10.1152/ajpcell.00011.2005
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of mitochondrial Ca2+ by nitric oxide in cultured bovine vascular endothelial cells

Abstract: -In the present study, we used laser scanning confocal microscopy in combination with fluorescent indicator dyes to investigate the effects of nitric oxide (NO) produced endogenously by stimulation of the mitochondria-specific NO synthase (mtNOS) or applied exogenously through a NO donor, on mitochondrial Ca 2ϩ uptake, membrane potential, and gating of mitochondrial permeability transition pore (PTP) in permeabilized cultured calf pulmonary artery endothelial (CPAE) cells. Higher concentrations (100 -500 M) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 54 publications
2
43
0
Order By: Relevance
“…Previous studies have demonstrated that in vascular endothelial cells, NO donor enhances ER Ca 2+ uptake and inhibits mitochondrial Ca 2+ overload. 38,39 Importantly, acetylcholine prevented the increased interaction within the VDAC1/Grp75/IP3R1 complex and mitofusin 2 expression, which explains, at least in part, its protective effect against endothelial injury induced by H/R. It is noteworthy that the decrease in mitochondrial Ca 2+ content paralleled a similar decrease in mitochondrial ROS levels by acetylcholine, suggestive of a possible correlation between mitochondrial Ca 2+ levels and ROS generation.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies have demonstrated that in vascular endothelial cells, NO donor enhances ER Ca 2+ uptake and inhibits mitochondrial Ca 2+ overload. 38,39 Importantly, acetylcholine prevented the increased interaction within the VDAC1/Grp75/IP3R1 complex and mitofusin 2 expression, which explains, at least in part, its protective effect against endothelial injury induced by H/R. It is noteworthy that the decrease in mitochondrial Ca 2+ content paralleled a similar decrease in mitochondrial ROS levels by acetylcholine, suggestive of a possible correlation between mitochondrial Ca 2+ levels and ROS generation.…”
Section: Discussionmentioning
confidence: 81%
“…Previous methods for evaluating stimulation-or stress-induced alterations in pulmonary endothelial cell ⌬ m using rhodamines or ratiometric probes have, in general, provided only indexes of relative changes, estimated from changes in fluorescence intensity (19,24,28,43,69). A common pitfall in interpreting such data is that the logarithmic form of the Nernst equation specifies that changes in fluorescence intensity (and, for ratiometric dyes, ratios derived from such changes) are not linearly proportional to changes in ⌬ m (45).…”
Section: Discussionmentioning
confidence: 99%
“…mathematical modeling; rhodamine 123; tetramethylrhodamine ethyl ester; multidrug transporter P-glycoprotein; hyperoxia PULMONARY ENDOTHELIAL mitochondrial and plasma membrane potentials (⌬ m and ⌬ p , respectively) are implicated in bioenergetic, metabolic, and signaling processes contributing to normal lung function and in injury (16,24,33,54,67,69). In most eukaryotic cells, ⌬ m is the major component of the mitochondrial electrochemical transmembrane potential and, as such, is involved in pulmonary endothelial mitochondrial ATP generation, regulation of calcium homeostasis, apoptosis, nitric oxide signaling, and other functions (19,58,60,61). Dissipation of ⌬ m is considered a hallmark of mitochondrial dysfunction in diverse cell types, including pulmonary endothelial cells exposed to oxidative stresses and bleomycin (24,33,43,54,69).…”
mentioning
confidence: 99%
“…Subsequent surface membrane permeabilization with the nonionic detergent digitonin removed cytoplasmic fluo-3. We developed this method and used it successfully to estimate [Ca 2ϩ ] m of endothelial cells (12,48). ] em from 0.1 to 10 M resulted in the increase of the mitochondria-trapped fluo-3 fluorescence (Fig.…”
Section: Measurements Of Intramitochondrial Free Camentioning
confidence: 99%